CONSUMPTION ANALYSIS OF SELECTED VEGETABLES AT HOUSEHOLD LEVEL IN YOGYAKARTA SEPCIAL PROVINCE - Kun Bunnavuth; Slamet Hartono; Irham Irham (Agro Ekonomi, 2006)
Objectives o the study are : (1) to analyze factors that affect the consumption of vegetables at low, intermediate, and high income levels of household in rural and urban areas of Yogyakarta Special Province, (2) to calculate the own proce elasticity with the consumption of each category of intermediate and high income levels.The study applies SUSENAS vegetables consumption data of the year os 2002 at Yogyakarta Special Province. The preferred vegetables consumed by people are spinach, string bean, carrot, cassava leaf anda egg plat. The total number of respondents is 1226 households at urban area. The censored regression analysis or tobit analysis the differention ofd low, intermediate and hiogh income households.The result of the study indicates that spinach, string bean, carrot, cassva leaf, and egg plant are the vegetables for most households in Yogyakarta Province with an inelastic demands. Furthermore, their consumption are affected by education level and the scale of families. The consumption of each type f vegetables in three levels of income both in rural and urban areas had less-affected by the changein proce of other vegetables (substitude vegetable). The result also shows that income of each households in the rural and urban had influenced the consumption of spinach, sring bean, carrot, cassava leaf, and egg plant.